2022
DOI: 10.1037/ppm0000318
|View full text |Cite
|
Sign up to set email alerts
|

The role of envy in linking active and passive social media use to memory functioning.

Abstract: Social media use has previously been shown to have negative implications for cognition. Scarce research has examined underlying pathways through which social media use may influence cognition. One potential pathway involves the consequences of social comparison, such that those who use social media more frequently may feel worse about themselves and more envious toward others. In turn, these negative socioemotional states could compromise memory. Further, whether an individual uses social media actively or pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…In this view, the meaning of the social media experience is different depending on how it is used 55 . When individuals use social media passively (consuming information) the effect of negative social comparison compromises memory, generating a lower social connection and higher stress 56 . On the other side, the active use of social media (recording and sharing personal experiences) facilitates rehearsal and meaning-making, also improving memory retention 57 .…”
Section: From "Us" To "Them": How Communication Technologies Are Unde...mentioning
confidence: 99%
“…In this view, the meaning of the social media experience is different depending on how it is used 55 . When individuals use social media passively (consuming information) the effect of negative social comparison compromises memory, generating a lower social connection and higher stress 56 . On the other side, the active use of social media (recording and sharing personal experiences) facilitates rehearsal and meaning-making, also improving memory retention 57 .…”
Section: From "Us" To "Them": How Communication Technologies Are Unde...mentioning
confidence: 99%
“…Envy refers to an individual’s feelings of inferiority, hostility, and resentment when a person lacks what others possess, which is categorized as an unpleasant emotion (Smith & Kim, 2007). When SNS users are passive, they are more likely to be exposed to others’ apparently flawless social information, which may elicit social comparisons and envious feelings when the users believe that other people’s lives are happier than theirs (Tandoc et al, 2015; Verduyn et al, 2020), and thus higher envy was also found to be linked to lower well-being (Ding et al, 2017), and lower cognitive functions (Sharifian et al, 2022). Therefore, we hypothesize that the relationship between PSNU and life satisfaction may be mediated by envy.…”
Section: Social Comparison Theory As a Main Theoretical Frameworkmentioning
confidence: 99%
“…As a result, we cannot help but be distracted from our everyday experiences (Dwyer et al, 2018; Smith, 2015). For example, people randomly assigned to enable notifications on their phone exhibit higher levels of inattention and hyperactivity than people who disable notifications (Kushlev et al, 2016; Stothart et al, 2015), and people who use social media or take photos during in-person experiences have worse memories of those experiences than people who do not (Sharifian et al, 2022; Soares & Storm, 2018; Tamir et al, 2018). Even when our phones are not buzzing and pinging in our ears, they can still decrease working memory and fluid intelligence because we have to suppress the temptation to check them (Ward et al, 2017).…”
Section: The Paradox Of (In)fallible Memory: Implications For Self-in...mentioning
confidence: 99%